Modified stress and temperature-controlled direct shear apparatus on soil-geosynthetics interfaces. Issue 3 (June 2021) - Chao, Zhiming; Fowmes, Gary
Abstract: In this paper, a bespoke stress and temperature controlled direct shear apparatus to test soil-geosynthetics interfaces is introduced. By adopting the apparatus, a series of 'rapid loading' shear tests and creep tests were conducted on the Clay – Geosynthetic Drainage layer (GDL) interfaces to assess the functionality of the apparatus. The experimental results indicate that, the modified apparatus can allow the shear deformation behaviour of soil-geosynthetics interfaces under environmental stress during thermal and drying-wetting cycles to be investigated, with a reliable performance. The resistance of Clay-GDL interfaces to shear deformation under the rapid loading of shear stress decreases after drying-wetting cycle and at elevated temperature. In the creep tests, the interfaces subjected to drying-wetting cycles and thermal cycles fail under a lower shear stress level than that of the interfaces without experiencing drying-wetting cycles and thermal cycles, respectively. The impacts of drying cycles on the horizontal displacement is significantly larger than that of wetting cycles. The first drying cycle has the largest impacts on the horizontal displacement than those of the following drying cycles. The impacts of drying alone on the horizontal displacement of Clay-GDL interfaces during drying cycles are small, and the main influence factor is the elevated temperature. Highlights: A bespoke stress and temperature controlled direct shear apparatus on soil-geosynthetics interfaces is introduced. The performance of the modified apparatus was validated by carrying out repetitive tests. The shear resistance of Clay-Geosynthetic Drainage Layer interfaces decreases after drying-wetting cycle. The impacts of drying cycle on the creep horizontal displacement is significantly larger than that of wetting cycle.